Association between hospital accreditation and healthcare providers’ perceptions of patient safety culture: a longitudinal study in a healthcare network in Brazil - Helidea de Oliveira Lima; Leopoldo Muniz da Silva; Leandro Reis Tavares; Ana Claudia Lopes Fernandes de Araújo; Laise Pereira Moreira; Vanessa de Melo Silva Torres; Fabiana Nogueira de Oliveira; Anthony M.-H. Ho; Deborah Simões; Glenio B. Mizubuti; Joaquim Edson Vieira (Israel Journal of Health Policy Research)
Abstract Background Enhancing security and dependability of health systems necessitates resource allocation, a well-defined infrastructure, and a steadfast commitment to ensuring its safety and stability over time. This study aimed to assess changes in patient safety culture over time (2014–2022) within a network of private hospitals in Brazil and to examine its association with the hospital accreditation process. The study utilized the Hospital Survey on Patient Safety Culture (HSOPSC) to measure healthcare professionals’ perceptions of patient safety culture. Methods The HSOPSC questionnaire was distributed to 71 hospitals between 2014 and 2022 with 259,268 responders. Hospitals were classified as accredited (AH) or non-accredited (NAH). A linear mixed-effects regression model was used to analyze the trend of dimension scores over time, accounting for both fixed and random effects to accommodate within-hospital correlations and variations across time points. Results Out of 12 dimensions analysed, 11 significantly improved, and one (“frequency of reported events”) remained unchanged over time (p = 0.84). Two dimensions had < 50% positive responses: “communication openness” (47.13% [38.19–58.73]) and “nonpunitive response to errors” (41.24% [34.13–51.98]). Safety culture improved among AH across all, but “frequency of reported events” (p = 0.12), dimensions. Among NAH, “frequency of reported events” decreased over time (p = 0.008) while other dimensions remained unchanged. Conclusion Our results suggest an improvement in patient safety culture within this network of private hospitals in Brazil from 2014 to 2022. While accreditation appears to be associated with fostering a culture of safety over time, our study does not establish a causal relationship. Additionally, non-accredited hospitals tended to report fewer adverse events, which may indicate underreporting and missed opportunities for healthcare system improvement through adverse event analysis.